2021
DOI: 10.1039/d0ra08690h
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble enhanced mass transfer efficiency of CO2 capture utilizing aqueous triethanolamine for enzymatic resorcinol carboxylation

Abstract: An inline method to investigate microbubble enhanced mass transfer and its effect on a model biocatalyst utilizing CO2 for carboxylation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…3 CO 2 capture is generally based on the use of a variety of sorbents, such as inorganic chemisorbents, MOFs, and organoamine adsorbents, which exhibited high theoretical uptake capacity, excellent catalytic performances, and generated valuable byproducts respectively. 4,5 In particular, CO 2 mineral sequestration deserves special attention as it is obtained directly. Du et al 6 found CO 2 has a strong affinity with montmorillonite, indicating a potential solution for CO 2 sequestration into a deep shale reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…3 CO 2 capture is generally based on the use of a variety of sorbents, such as inorganic chemisorbents, MOFs, and organoamine adsorbents, which exhibited high theoretical uptake capacity, excellent catalytic performances, and generated valuable byproducts respectively. 4,5 In particular, CO 2 mineral sequestration deserves special attention as it is obtained directly. Du et al 6 found CO 2 has a strong affinity with montmorillonite, indicating a potential solution for CO 2 sequestration into a deep shale reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on triethanolamine (TEOA), which is a well-known sacrificial reductant for photocatalysis 7 10 and a CO 2 capture agent. 11 TEOA possesses synthetic and industrial advantages attributed to its low vapor pressure (1.3 Pa at 20 °C), high boiling point (335 °C), high flash point (199 °C), and low toxicity (orl-mus LD 50 = 5846 mg/kg). 12…”
Section: Table 1 Optimization Of the Reaction Conditionsmentioning
confidence: 99%
“…In this study, we focused on triethanolamine (TEOA), which is a well-known sacrificial reductant for photocatalysis 7,10 and a CO 2 capture agent. 11 TEOA possesses synthetic and industrial advantages attributed to its low vapor pressure (1.3 Pa at 20 °C), high boiling point (335 °C), high flash point (199 °C), and low toxicity (orl-mus LD 50 = 5846 mg/kg). 12 We recently reported the C-H activation of thiophenes and indoles, the Mizoroki-Heck reaction, 13 and the hydrogenation of alkenes 14 using a silicon nanowire array Pd (Si-NA-Pd) catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al found that microbubble decomposition of pollutants including phenol and nitrobenzene is markedly more efficient than conventional bubbling in terms of ozone consumption across a broad pH range . Similarly, it was found that this highly efficient aeration technique has the potential to reduce the necessary CO 2 gas feed as well as the waste of unreacted CO 2 in the biocatalytic reaction . Most of these studies were carried out in bubble columns up to date.…”
Section: Introductionmentioning
confidence: 99%